The self and the world. Aspects of the aesthetics and politics of contemporary North American literary memoir by women - Rzepa, Agnieszka; Drewniak, Dagmara; Macedulska, Katarzyna (Wydawnictwo Naukowe UAM, 2018)
The book constitutes an attempt at a selective, but far-ranging analysis of the aesthetics and politics of memoirs written by Canadian and US women of different racial and ethnic backgrounds since 1990. The study focuses on memoirs by experienced writers, consciously deploying in their texts a number of literary, visual and paratextual devices. The aim is to illuminate the ways in which they make sense of their experience and how they endow it with a particular narrative shape, with special focus on the implicit and explicit ideological baggage of the memoirs. An important aspect of the project is the critical reflection on the nature of memory that emerges from the selected texts in connection with both individual and collective history. Special focus falls on configurations of gender and race/ethnicity in the contexts of the two multicultural North American societies, and their influence on the process of self-fashioning.
Keywords: memoir; life-writing; memoir by women writers; female memoir in Canada and the USA; Canadian literature